2015
DOI: 10.1016/j.bbi.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine preferentially modulates memory CD8 T cell function inducing inflammatory cytokine production and reducing proliferation in response to activation

Abstract: Background Norepinephrine (NE) is one of the primary catecholamines of the sympathetic nervous system released during a stress response and plays an important role in modulating immune function. NE binds to the adrenergic receptors on immune cells, including T cells, resulting in either suppressed or enhanced function depending on the type of cell, activation status of the cell, duration of NE exposure and concentration of NE. Here, we aim to analyze the effects of NE on the functionality of naïve (Tn), centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 44 publications
8
100
1
1
Order By: Relevance
“…By binding to various cellular receptors, epinephrine and norepinephrine may induce profound metabolic changes via increased glycolysis and lipolysis, hypertensive changes via arterial smooth muscle constriction and increased cardiac output, 43 and proinflammatory changes via increased expression of proinflammatory cytokines. 44 Last, our results suggest that PM exposure may stimulate the secretion of melatonin, a hormone that regulates circadian cycle and has multiple cardioprotective properties. 45 It has also been suggested that melatonin has antihypertensive effects probably because of its anti-inflammatory and reactive oxygen species scavenging properties, and its capability in improving endothelial function and interacting with central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to various cellular receptors, epinephrine and norepinephrine may induce profound metabolic changes via increased glycolysis and lipolysis, hypertensive changes via arterial smooth muscle constriction and increased cardiac output, 43 and proinflammatory changes via increased expression of proinflammatory cytokines. 44 Last, our results suggest that PM exposure may stimulate the secretion of melatonin, a hormone that regulates circadian cycle and has multiple cardioprotective properties. 45 It has also been suggested that melatonin has antihypertensive effects probably because of its anti-inflammatory and reactive oxygen species scavenging properties, and its capability in improving endothelial function and interacting with central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding stress effects on immune cells, our data suggested that (1) glucocorticoid seem to be the common link between the effects of stress on immunity; in fact, many of the effects on circulating leukocytes described during stress may be ascribed to increased levels of this hormone (Costa-Pinto & Palermo-Neto, 2010); (2) despite the well-known immunosuppressive properties of glucocorticoids, it is known that these hormones also possess opposing effects that emphasize a bimodal hormonal regulation of the immune responses (Petrella et al, 2014); (3) a growing body of evidence indicates that the SNS modulates the immune system functions; however, the effect of NOR on immune cells appears to be more complex, as NOR can have either a stimulatory or inhibitory effect depending on the type of immune cell, their activation status, the duration of NOR exposure and the dose of NOR employed (Slota et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in CD8 + cell numbers was also found on ED21 in birds of the PCS group of this study. Recent work using in vitro NOR treatment and CD8 + T cells (Slota et al, 2015) showed a catecholamine-induced reduction in the expression of IFN-γ and IL-2 in NOR treated memory CD8 + T cells; according to these authors, the decreased productions of IL-2 and IFN-γ might have contributed to the modest decrease in the immune cell number found in the NOR-treated cells. These findings suggest that NOR might play a pivotal role in altering the proliferation of memory CD8 + T cells.…”
Section: Low Percentages Of Cd3mentioning
confidence: 99%
“…Moreover such a hypothesis considers the influence of genotype in isolation. It ignores the potential influence of phenotype (the sympathetic stress response) which influences levels of essential minerals, vitamins and cofactors; lowers levels of T-cells and immunochemicals in response to a particular stress or stressor [38] [39]; and facilitates the onset and progression of a particular viral infection, the direct or indirect establishment of an autoimmune response [25] and the subsequent development of type 1 diabetes.…”
Section: Discussion Of the Different Factors Which Influence The Onsementioning
confidence: 99%